Suplementação continuada para produção de machos da raça Jersey superjovens em pastagens - Severo, Igor Kieling (2025)
This work aimed to evaluate pasture characteristics, animal performance and behavior, as well as the carcass characteristics of Jersey dairy males fed supplementation levels on pasture. The experiment took place from October 2019 to November 2020 and was divided into two phases. Phase I refers to rearing and phase II to finishing. The experimental design was entirely randomized with three treatments (supplementation levels) and three replications. The supplementation levels used were 8, 11 and 14 g/kg body weight of a commercial supplement with 12% crude protein. In phase I, the experimental area used was 1.42 ha, consisting of aruana grass pasture. In phase II, the area used was 2.25 ha, consisting of black oat + ryegrass pasture established by over-seeding the aruana grass pasture. In both phases, nine paddocks with drinking and feeding troughs were used. The animals used were 26 Jersey cattle aged 6.68 months and weighing 140 kg (phase I) and 13.9 months and weighing 236.9 kg (phase II). A continuous stocking system with variable loading was used. In the rearing phase, pasture height, mass, supply and daily forage accumulation rate were not altered (P>0.10) by supplementation levels. Animal load and weight gain per area were lower for the level of 08 g of supplement/kg of body weight compared to the others.The percentage of leaf, thatch and the leaf/thickness ratio of the aruana grass pasture were not altered (P>0.10) by the levels of supplementation. The proportion of dead material was higher for the 14 g/kg supplementation level (P>0.10). Grazing time, other activities, feeding stations, steps/minute and mouthfuls/EA were altered (P<0.10) by supplementation levels. Average daily weight gain and body weight at the end of the rearing period were not altered (P>0.10) by supplementation levels. In the finishing phase, pasture height, forage mass, forage supply and daily forage accumulation rate were not altered (P>0.10) by supplementation levels. Animal load, average daily weight gain and weight gain per area were higher (P<0.10) at the supplementation level of 14 g/kg body weight compared to the lowest supplementation level (08 g/kg body weight), with no differences for the other comparisons between treatments. The leaf:stalk ratio and the percentages of each component were not altered (P<0.10) by the levels of supplementation. The dry matter and crude protein content in both phases did not differ (P<0.10) between supplementation levels. Ingestive behavior in the finishing phase was not altered (P>0.10) by supplementation levels. Slaughter age was lower for supplementation with 11 g/kg than for the lowest level of supplementation, with no difference for the other comparisons. The subcutaneous fat thickness of the carcasses was similar between the higher levels of supplementation, being higher (P<0.10) for supplementation with 11 g/kg of body weight compared to supplementation with 8 g/kg of body weight. Supplementation levels of between 11 and 14 g/kg body weight are recom- mended for super-precocious castrated males of the Jersey breed, as they provide adequate nutrients to optimize weight gain, feed efficiency and productive performance in grazing systems.